Simulating the hydrological response to climate change in a Southern Alberta watershed - Forbes, Katharine A.; University of Lethbridge. Faculty of Arts and Science (Lethbridge, Alta. : University of Lethbridge, Dept. of Geography, 2007)
The current body of research in western North America indicates that water resources in the Oldman Basin are vulnerable to the impacts of climate change. The objectives of this thesis were to parameterize and verify the ACRU hydrological modelling system for the 256 km2 Beaver Creek watershed, a tributary to the Oldman River. The ACRU model successfully simulated monthly volumes of the observed hydrological record (r2 =0.78), and simulated the behaviour of the mean annual hydrograph with sufficient accuracy to assess the mean change in future hydrological response over 30-year simulation periods. A range of global climate model (GCM) projections were used to perturb the 1961-1990 baseline climate record using the delta downscaling technique, which resulted in the input for future hydrological simulations. Five potential future hydrological regimes were compared to the 1961-1990 baseline conditions to determine the net effect of climate change on the hydrological regime of the Beaver Creek catchment over three time periods of 2020, 2050 and 2080. Despite annual projections for a warmer and wetter climate in this region, the majority of the simulations indicated that the seasonal changes in climate resulted in a shift of the seasonal streamflow distribution. The results indicated an increase in winter and spring streamflow volumes and a reduction of summer and fall streamflow volumes over all time periods, relative to the baseline conditions (1961-1990) in 4 of the 5 scenarios.